Defects in myosin VB are associated with a spectrum of previously undiagnosed low γ‐glutamyltransferase cholestasis. Issue 5 (23rd March 2017) - Qiu, Yi‐Ling; Gong, Jing‐Yu; Feng, Jia‐Yan; Wang, Ren‐Xue; Han, Jun; Liu, Teng; Lu, Yi; Li, Li‐Ting; Zhang, Mei‐Hong; Sheps, Jonathan A.; Wang, Neng‐Li; Yan, Yan‐Yan; et al.
Abstract : Hereditary cholestasis in childhood and infancy with normal serum gamma‐glutamyltransferase (GGT) activity is linked to several genes. Many patients, however, remain genetically undiagnosed. Defects in myosin VB (MYO5B; encoded by MYO5B ) cause microvillus inclusion disease (MVID; MIM251850) with recurrent watery diarrhea. Cholestasis, reported as an atypical presentation in MVID, has been considered a side effect of parenteral alimentation. Here, however, we report on 10 patients who experienced cholestasis associated with biallelic, or suspected biallelic, mutations in MYO5B and who had neither recurrent diarrhea nor received parenteral alimentation. Seven of them are from two study cohorts, together comprising 31 undiagnosed low‐GGT cholestasis patients; 3 are sporadic. Cholestasis in 2 patients was progressive, in 3 recurrent, in 2 transient, and in 3 uncategorized because of insufficient follow‐up. Liver biopsy specimens revealed giant‐cell change of hepatocytes and intralobular cholestasis with abnormal distribution of bile salt export pump (BSEP) at canaliculi, as well as coarse granular dislocation of MYO5B. Mass spectrometry of plasma demonstrated increased total bile acids, primary bile acids, and conjugated bile acids, with decreased free bile acids, similar to changes in BSEP‐deficient patients. Literature review revealed that patients with biallelic mutations predicted to eliminate MYO5B expression were more frequent in typical MVID than in isolated‐cholestasis patients (11 of 38 vs. 0 of 13). Conclusion : MYO5B deficiency may underlie 20% of previously undiagnosed low‐GGT cholestasis. MYO5B deficiency appears to impair targeting of BSEP to the canalicular membrane with hampered bile acid excretion, resulting in a spectrum of cholestasis without diarrhea. (Hepatology 2017;65:1655‐1669).